Combined nitrogen retention in an agricultural river system - Allaway, Christopher (University of Ottawa (Canada), 2006)
Since combined nitrogen is a pollutant in streams, rivers and coastal areas, conditions that favour nitrogen removal were identified. The importance of stream depth as a predictor of a reach's capacity to remove nitrogen was tested in the South Nation watershed (3915 km2), an agricultural watershed in eastern Ontario. Combined nitrogen (N) retention was estimated in 48 reaches across the watershed which varied in discharge (0.0008--118 m3 s-1), length (350 m to 5.2 km) and size from headwaters to the outflow of the South Nation River at the Ottawa River. Retention dynamics were also investigated within a few sites over the summer season. Retention efficiency (expressed as a percentage of inputs) varied widely for nitrate from almost complete removal within a reach to reaches acting as a net source. A narrower range in percent retention and loading was observed for total nitrogen (TN) among the sites suggesting that some forms of combined nitrogen are relatively inert. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.; Environmental Sciences.